The Effect of Product Quality, Brand Image, and Influencer Endorsement on Purchase Decisions for Skintific Skincare Products - Firdausa, Natasya Amatul; Baskoro, Heru (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The objective of this study is to analyze the partial and simultaneous effects of product quality, brand image, and influencer endorsement on purchasing decisions for Skintific products. The population for this research consists of all consumers who have used Skintific products at least once in the Gresik region. The analysis method involves primary data collected from 150 respondents using accidental sampling. The tests conducted include validity, reliability, normality, multicollinearity, heteroskedasticity, multiple linear regression, F-test, t-test, and coefficient of determination test. The study concludes that product quality, brand image, and influencer endorsement have a positive and significant impact on purchasing decisions when analyzed individually.